Expression and Prognostic Significance of Neurotrophins and Their Receptors in Canine Mammary Tumors. Issue 4 (July 2020) - Rogez, Bernadette; Pascal, Quentin; Bobillier, Audrey; Machuron, François; Toillon, Robert-Alain; Tierny, Dominique; Chopin, Valérie; Le Bourhis, Xuefen
Accumulating data highlight the role of neurotrophins and their receptors in human breast cancer. This family includes nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), both synthetized as proneurotrophins (proNGF and proBDNF). (pro)NGF and (pro)BDNF initiate their biological effects by binding to both their specific receptors TrkA and TrkB, respectively, and the common receptor p75 NTR . Currently, no data are available about their expression and potential role in canine mammary tumors. The aim of this study was to investigate expression of proNGF and BDNF as well as their receptors TrkA, TrkB, and p75 NTR in canine mammary carcinomas, and to correlate them with clinicopathological parameters (grade, histological type, lymph node status, recurrence, and distant metastasis) and survival. Immunohistochemistry was performed on serial sections of 96 canine mammary carcinomas with antibodies against proNGF, BDNF, TrkA, TrkB, and p75 NTR . Of the 96 carcinomas, proNGF expression was detected in 71 (74%), BDNF in 79 (82%), TrkA in 94 (98%), TrkB in 35 (37%), and p75 NTR in 44 (46%). No association was observed between proNGF, BDNF, or TrkA expression and either clinicopathological parameters or survival. TrkB and p75 NTR expression were associated with favorable clinicopathological parameters as well as better overall survival.